PROFIL VIRUS DENGUE DI SURABAYA TAHUN 2008–2009 - aryati .; Puspa Wardhani (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
Four serotypes of dengue viruses (DENV) 1–4 are mosquito-borne human pathogens that cause widespread epidemics withconsiderable morbidity and mortality. The aim of this study was to evaluate the dengue serotypes profile, which were circulating inSurabaya. This research has been carried out consisting of 360 samples from patients with dengue virus infections, according the WorldHealth Organization (WHO) criteria. These sera were collected from patients Dr. Soetomo Hospital and private laboratory in Surabayafrom 2008–2009. From 360 samples, 68 samples (18.9%) were undifferentiated fever, 53 samples (14.7%) were dengue fever, 239samples (66.4%) were dengue hemorrhagic fever. From 58 Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) samples, 25samples (43%) were positive, consisting of 52% DEN-2, 20% DEN-1, 16% DEN-3 and 12% DEN-4. These results showed that fourserotypes are circulating in Indonesia, dominated by DEN-2, followed by DEN-1, DEN-3 and DEN-4.